1) Zapisz wyrażenia bez nawiasów i oblicz ich wartość.
a) 7 + (-9)
b) (-4) - (-4)
c) -4 + (-3)
d) (-12) + (-18)
e) -(-7) - (-7)
f) (-31) - (-9)
g) -8 - (-(-2))
h) 4 - (-5) + (-8)
i) -9 + (-42)

2) Oblicz.
a) 5 + (-4)
b) 6 - (-7)
c) -21 + (-4)
d) -10 - (-20)
e) -12 + (-27)
f) 3 - 24
g) -37 + 48
h) 15 + (-27)
i) -9 + (-42)

Pilne.

3

Odpowiedzi

2010-01-07T19:50:18+01:00
7-9=2
-4+4=0
-4-3=-7
-12-18=-30
7+7=14
-31+9=-22
-8-2=-10
4+5-8=1
-9-42=-51

1
13
-25
10
-39
-21
11
-12
-51
6 3 6
Najlepsza Odpowiedź!
2010-01-07T19:50:18+01:00
A) 7 + (-9)=7-9=-2
b) (-4) - (-4)=-4+4=0
c) -4 + (-3)=-4-3=-7
d) (-12) + (-18)=-12-18=-30
e) -(-7) - (-7)=7+7=14
f) (-31) - (-9)=-31+9=-22
g) -8 - (-(-2))=-8-2=-10
h) 4 - (-5) + (-8)=4+5-8=1
i) -9 + (-42)=-9-42=-51

2) Oblicz.
a) 5 + (-4)=5-4=1
b) 6 - (-7)=6+7=13
c) -21 + (-4)=-21-4=-25
d) -10 - (-20)=-10+20=10
e) -12 + (-27)=-12-27=-37
f) 3 - 24=-21
g) -37 + 48=11
h) 15 + (-27)=15-27=-12
i) -9 + (-42)=-9-42=-51
17 3 17
2010-01-07T19:51:37+01:00
1) Zapisz wyrażenia bez nawiasów i oblicz ich wartość.
a) 7 + (-9) = 7 - 9= -2
b) (-4) - (-4) = -4 + 4 = 0
c) -4 + (-3) = - 4 - 3 = - 7
d) (-12) + (-18) = -12 - 18 = -30
e) -(-7) - (-7) = 7 + 7 = 14
f) (-31) - (-9) = -31 + 9 = -22
g) -8 - (-(-2)) = -8 - 2 = -10
h) 4 - (-5) + (-8) = 4 + 5 - 8 = 1
i) -9 + (-42) = -9 - 42 = -51

2) Oblicz.
a) 5 + (-4) = 5 - 4 = 1
b) 6 - (-7) = 6 + 7 = 13
c) -21 + (-4) = 21 - 4 = 17
d) -10 - (-20) = -10 + 20 = 10
e) -12 + (-27) = -12 - 21 = - 33
f) 3 - 24 = -21
g) -37 + 48 = 11
h) 15 + (-27) = 15 - 27 = -12
i) -9 + (-42) = -9 - 42 = - 51
6 4 6